AEGIS: A panchromatic study of IRAC-selected extremely red objects with confirmed spectroscopic redshifts - Wilson, G; Huang, J; Fazio, G; Yan, R; Koekemoer, A; Salim, S; Faber, S; Lotz, J; Willmer, C; Davis, M; Coil, A; Newman, J; et al. (Institute of Physics Publishing, 2007)
We study 87 extremely red objects (EROs), selected both to have color redder than R - [3.6] = 4.0 and to have confirmed spectroscopic redshifts. Together, these two constraints result in this sample populating a fairly narrow redshift range at 0.76 < z < 1.42. The key new ingredient included here is deep Spitzer Space Telescope Infrared Array Camera (IRAC) data. Based on [3.6] - [8.0] color, we demonstrate that it is possible to classify EROs as early-type galaxies, dusty starburst galaxies, or active galactic nuclei (AGNs; power-law types). We present ultraviolet-to-mid-infrared spectral energy distributions (SEDs) and Advanced Camera for Surveys (ACS) images, both of which support our simple IRAC color classification. © 2007. The American Astronomical Society. All rights reserved.